2011
DOI: 10.1039/c1dt10696a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of spin crossover behaviour in iron(iii) complexes involving pentadentate Schiff bases and pseudohalides

Abstract: Investigations on a series of eight novel mononuclear iron(III) Schiff base complexes with the general formula [Fe(L(5))(L(1))]·S (where H(2)L(5) = pentadentate Schiff-base ligand, L(1) = a pseudohalido ligand, and S is a solvent molecule) are reported. Several different aromatic 2-hydroxyaldehyde derivatives were used in combination with a non-symmetrical triamine 1,6-diamino-4-azahexane to synthesize the H(2)L(5) Schiff base ligands. The consecutive reaction with iron(III) chloride resulted in the preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 36 publications
5
46
0
Order By: Relevance
“…These compounds form stable and variety complexes with the majority of transition metal ions that exhibit various electronic and structure characteristics [5][6][7][8][9]. Therefore, the research area containing the coordination compounds with azomethine ligands as main characters is widely expansive especially due to their potential interest roles in various interdisciplinary fields such as: structural features [10,11], efficient different catalytic processes in various organic reactions [12][13][14], models of the metal ion coordination sites in metalloproteins or enzymes at bioinorganic chemistry [15][16][17], magnetochemistry [18][19][20], corrosion inhibitors [21] and nonlinear optical materials [22][23][24]. Second-Order NLO organic materials such as Schiff base compounds have recently attracted attention owing to their potential applications in computers, optical communication and medical imaging [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds form stable and variety complexes with the majority of transition metal ions that exhibit various electronic and structure characteristics [5][6][7][8][9]. Therefore, the research area containing the coordination compounds with azomethine ligands as main characters is widely expansive especially due to their potential interest roles in various interdisciplinary fields such as: structural features [10,11], efficient different catalytic processes in various organic reactions [12][13][14], models of the metal ion coordination sites in metalloproteins or enzymes at bioinorganic chemistry [15][16][17], magnetochemistry [18][19][20], corrosion inhibitors [21] and nonlinear optical materials [22][23][24]. Second-Order NLO organic materials such as Schiff base compounds have recently attracted attention owing to their potential applications in computers, optical communication and medical imaging [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The former μ-4,4 -bipy type were first reported by Hayami et al 101,102 From a theoretical and data fitting perspective, Boča et al 48,100 found that the Ising thermodynamic model discussed above for Fe II Fe II SCO species would not fit the CN-bridged Fe III Fe III χ M T (μ eff ) vs. T or isothermal magnetization, M vs. H data at 2 K. So, they developed a new and more extensive model that, while it used many parameters, was capable of simultaneously fitting magnetic susceptibility, magnetisation, n HS and Mössbauer spectral data. But first, we briefly discuss the experimental data and start with mononuclear 'precursors', the magnetic data of which could be fitted by use of Ising models.…”
Section: Theoretical and Experimental Developments In Dinuclear Fe IImentioning
confidence: 99%
“…Complexes 100 Observables were χ M T vs. T and M vs H at 2 and 4.6 K. The CN − compounds were LS d 5 (S = 1 / 2 ) and displayed typical LS Fe III -N and Fe III -O distances and small octahedral distortions ∼25 • . The HS examples had longer Fe-N/O bond lengths and higher ∼56 • and displayed typical HS 6 A 1g zero-field split magnetism with decreases observed in χ M T below ∼5 K, the D parameters <1 cm −1 , confirmed by the magnetisation isotherms.…”
Section: Theoretical and Experimental Developments In Dinuclear Fe IImentioning
confidence: 99%
See 1 more Smart Citation
“…The transition of spin states is an entropy-driven process, which can be triggered by external parameters such as temperature [1], pressure [2], magnetic [3] or electric field [4,5], and by irradiation with the visible/near—infrared [6] or even X-ray [7] range. Up to now, the occurrence of the SCO phenomenon was observed for central atoms in coordination compounds of 3d 4 – 3d 7 electronic configuration, whereby the spherical symmetry of d -orbitals was broken into the e g and t 2 g orbital subsets by the tetragonal bipyramidal environment of the N 6 coordination environment.…”
Section: Introductionmentioning
confidence: 99%